2023
DOI: 10.1021/acs.jafc.2c08378
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Alleviates Perfluorooctanesulfonic Acid-Induced Cardiomyocyte Apoptosis by Maintaining Mitochondrial Dynamic Balance and Energy Metabolic Homeostasis

Abstract: Perfluorooctanesulfonic acid (PFOS), a fluorine-containing organic compound, can be widely detected in the environment and living organisms. Accumulating evidence has shown that PFOS breaks through different biological barriers resulting in cardiac toxicity, but the underlying molecular mechanisms remain unclear. Cannabidiol (CBD) is a nonpsychoactive cannabinoid without potential adverse cardiotoxicity and has antioxidant and anti-inflammatory properties that reduce multiorgan damage and dysfunction. For thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 60 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Cannabidiol also maintains mitochondrial morphology by modulating mitochondrial fission and fusion. ( Li M. et al, 2022 ; Wang et al, 2023 ; Xu et al, 2023 ). For example, CBD can inhibit the expression of fission genes including mitochondrial fission 1 protein (FIS1), dynamin-1-like protein (DRP1) and optic atrophy type 1 (OPA1), and increase the expression of fusion genes, such as mitochondrial elongation factor (MIEF1), mitofusin 1 (Mfn1) and mitofusin 2 (Mfn2), in vitro model of pulmonary hypertension ( Lu et al, 2021 ).…”
Section: Inhibition Of Ros/rns Generation By Cbd: Relevance For Ichmentioning
confidence: 99%
“…Cannabidiol also maintains mitochondrial morphology by modulating mitochondrial fission and fusion. ( Li M. et al, 2022 ; Wang et al, 2023 ; Xu et al, 2023 ). For example, CBD can inhibit the expression of fission genes including mitochondrial fission 1 protein (FIS1), dynamin-1-like protein (DRP1) and optic atrophy type 1 (OPA1), and increase the expression of fusion genes, such as mitochondrial elongation factor (MIEF1), mitofusin 1 (Mfn1) and mitofusin 2 (Mfn2), in vitro model of pulmonary hypertension ( Lu et al, 2021 ).…”
Section: Inhibition Of Ros/rns Generation By Cbd: Relevance For Ichmentioning
confidence: 99%
“…For instance, ROS triggers oxidative stress, which in turn encourages the release of cytochrome C from mitochondria, activating apoptosis . Apoptosis is associated with live ROS, which at high levels cause oxidative damage to cells, damaging DNA and proteins . ROS-induced autophagy regulates the proliferation and differentiation of porcine trophoblast ectodermal cells .…”
Section: Discussionmentioning
confidence: 99%
“…67 Apoptosis is associated with live ROS, which at high levels cause oxidative damage to cells, damaging DNA and proteins. 68 ROS-induced autophagy regulates the proliferation and differentiation of porcine trophoblast ectodermal cells. 69 In this study, we found that the expression of AVM-induced liver autophagy and apoptosis-related proteins was significantly suppressed in carp liver after the use of ROS inhibitors, suggesting that ROS mediates AVM-induced apoptosis and autophagy in carp liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…All of the primers of mRNAs and miRNAs (Tables 5 and 6) are designed using Primer Premier 6.0 software (PREMIER Bio‐soft International) and synthesized by Sangon Biotech (Shanghai) Co., Ltd. The comparative 2 −△△CT method with glyceraldehyde 3‐phosphate dehydrogenase and U6 as an endogenous control was used to calculate gene expression (Wang et al, 2023).…”
Section: Methodsmentioning
confidence: 99%